Prevalence of Extended Spectrum Beta Lactamases (ESBL) and Metallo Beta Lactamases (MBL) Mediated Resistance in Gram Negative Bacterial Pathogens (Tribhuvan University Journal of Microbiology, 2018)
Objectives: This study was conducted to determine the prevalence of multi-drug resistance (MDR) along with Extended Spectrum β-lactamase (ESBL) and Metallo β-lactamase (MBL) producing gram negative bacterial isolates among the patients attending Shahid Gangalal National Heart Centre, Kathmandu, Nepal.Methods: This cross-sectional study was carried out from June to December; 2016. Altogether 977 clinical specimens were processed for analysis of bacteriological profile and the isolates were identified by culture, morphological and biochemical tests. Antibiotic susceptibility testing of the isolates was performed by Kirby Bauer disc diffusion methods following Clinical and Laboratories Standard Institute guideline and the isolates were tested for ESBL and MBL by combined disk method.Results: out of 977 clinical specimens, 254 (25.99%) were found to be gram negative bacterial isolates, among them Klebsiella pneumoniae 83 (32.67%) was the most predominant organism followed by E. coli 51 (20.07%), Pseudomonas aeruginosa 36 (14.17%), K. oxytoca 32 (12.59%), Proteus mirabilis 13 (5.11%) and P. vulgaris 13 (5.11%), Acinetobacter spp. 11 (4.33%), Citrobacter spp. 10 (3.93%) and Enterobacter spp. 5 (1.96%) respectively. 83 (32.67%) isolates were found to be MDR, 38(14.96%) were positive for ESBL while 19 (7.48%) were MBL producer.Conclusion: The determent drug resistance among ESBL and MBL producers, reflect the extensive use of antibiotics possessing difficulties in therapeutic potions in hospital setting which might be overcome by proper microbiological analysis of pathogenic isolates and judicious use of antibiotics for emergence of resistance strains.